Acacia mangium Willd. and Melaleuca cajuputi Powell as potential heavy metal accumulators in sewage sludge-contaminated soils - Nik Jaafar, Nik Mohd Shibli (2014)
Waste disposal in Malaysia faces serious challenges and has caused soil pollution. There are currently over 6 million cubic meters of sewage sludge in Malaysia requiring safe disposal. Phytoremediation is the use of plants to remediate polluted soils and this approach has not been practised in Malaysia. This study aimed to assess the potential and viability of two tropical timber species to remediate heavy metal contaminated soil. A greenhouse and field experiments were conducted to evaluate Acacia mangium Willd and Melaleuca cajuputi Powell to extract heavy metals namely Zinc (Zn), Copper (Cu) and Cadmium (Cd) from sewage sludge contaminated soils. Results showed that under greenhouse conditions, both species are tolerant to Zn, Cu and Cd and could accumulate high concentrations of these elements especially in the roots. The leaves of A. mangium accumulated 156.96mg/kg of Zn and 135.20mg/kg in M. cajuputi leaves. In the roots, the concentrations were 266.25mg/kg and 137.19mg/kg, respectively. Accumulation of Zn in the stems of A. mangium was 102.24mg/kg and 107.50mg/kg for M. cajuputi. Accumulation of Cu in the leaves of A. mangium was higher (20.74mg/kg) than in M. cajuputi (9.53mg/kg) and in the roots it was 25.29mg/kg and 20.85mg/kg, respectively. The stems of M. cajuputi accumulated more Cu (19.27mg/kg) than A. mangium (14.01mg/kg). The accumulation of Cd in the stems and roots were greater in M. cajuputi with concentrations of 1.78mg/kg and 2.05mg/kg, compared in A. mangium at 1.51 mg/kg and 1.66 mg/kg, respectively. Accumulation of Cd in the leaves of A. mangium was slightly higher (1.93mg/kg) than M. cajuputi (1.66mg/kg). The study under field conditions shows that stems of A. mangium accumulated up to 130.0mg/kg of Zn and in the leaves it was up to 100.0 mg/kg. Accumulation of Cu by A. mangium in the stems was about 17.0mg/kg and in the leaves was about 22.0mg/kg. The accumulation of Cd in the stems was 1.23 - 1.62mg/kg. However, Cd accumulation in the A. mangium leaves was 0.3 - 1.6mg/kg. Accumulation of Zn in M. cajuputi leaves was higher (80 - 100.0mg/kg) than in the stems (60 - 70.0mg/kg). The stems of M. cajuputi accumulated 9.0 - 22.0mg/kg Cu and in the leaves it was 4.0 - 15.0mg/kg. While Cd accumulation in the stems was 0.30 - 0.45mg/kg and in leaves it was 0.25 - 0.4mg/kg. In the greenhouse experiment, both species show low ability to accumulate Cu and Cd as reflected by low BCF (BCF ≤ 1) but translocate high amounts of all three elements to the shoots as shown by high TF (TF ≥ 1). On the other hand, in the field experiment, A. mangium showed good ability (BCF ≥ 1) for extracting Zn and Cd but only Zn for M. cajuputi. However, M. cajuputi stems accumulated more heavy metals compared to the leaves indicating that the heavy metals can be stored for a longer period. Phytoextraction efficiency of A. mangium was better than M. cajuputi as the biomass generated in the field experiment after 12 months was about 72 tonnes/ha compared to only 4 tonnes/ha in case of M. cajuputi. It was estimated that A. mangium is able to extract 16.49kg/ha Zn, 2.80kg/ha Cu and 0.12kg/ha Cd per year whereas M. cajuputi could only extract 12.91kg/ha/year, 2.65kg/ha/year and 0.06kg/ha/year of the three heavy metals, respectively. The trees also affect mobility of Zn, Cu and Cd in the soil as shown by high fractions of the ionic and reducible forms of these metals at the beginning. The mobility reduced at the end of the study where these two fractions were reduced to about 2% from 69% for Cu and about 23% from 53% for Cd but Zn remained the same. Principal component analysis of the soil chemical properties shows humic acids played an important role (1st component) in heavy metal stabilization in the soil after planting and the effects of pH and CEC on metal mobility were reduced (2nd component) thus lowering the risk of these elements from spreading. The cost-effective economic evaluation of A. mangium in this study for a 10-year rotation period was estimated to cost only MYR 231,800.00/ha compared to MYR 3 million/ha using the conventional soil remediation techniques. Within this period, over 35, 800 tonnes of carbon/ha was produced that could generate returns of about MYR 1.9 million/ha. Timber production was estimated at 25,300m3/ha and could generate returns of about MYR 6.33 million/ha. Hence, this study shows that phytoremediation using trees species is economically viable for disposal of sewage sludge.